(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
The life insurance companies need a sound system to use it in selecting Insurable risks so they can avoid or reduce possible losses that may be insured to a minimum levels , But the application within IRAQI INSURANCE COMPANY reflects that it still depends on a traditional ways in the procedures used to select that risks . This research represents an attempt to put acceptable suggestions about developing a system for selecting insurable risks which used now by iraqi insurance company by recognizing the risks of life insurance , determining kinds of risks which can difined as normal and upnormal risks , rectification of the medical tests schdul adopted now by the company , and searching for practical and applied bases that can be depend on for selecting and assessing the risk at checking the applications for life insurance .